(untitled) (Educa Journal of Studies, 2026)
This article examines the role of the digital educational environment in enhancing an individual’s intellectual development. In the context of rapid technological advancement, the integration of digital tools, online learning platforms, and electronic educational resources has become an essential component of the modern educational process. The study focuses on how digital learning environments support the development of analytical thinking, independent learning skills, creativity, and effective information management among students. Furthermore, the article discusses the opportunities created by digital technologies in education as well as the challenges related to their implementation in the learning process.